Polish-German preschoolers develop and use heritage Polish differently depending on whether they heard German from birth or not - De Houwer, Annick (Frontiers in Psychology, 2023)
This study assessed the language proficiency and use of a hitherto underinvestigated group, viz., 28 3.5-year-olds growing up with Polish as a heritage language and German as societal language. All children heard Polish from birth in the home but half the children also heard German from birth (Bilingual First Language Acquisition, BFLA) while the other half added German through preschool (Early Second Language Acquisition, ESLA). All children attended German preschools. Data collection relied on an online survey filled out by 28 mothers and 20 fathers. Its findings contribute both methodological and substantive insights. Methodologically the study showed large discrepancies between parental answers to general versus detailed questions. This has important repercussions for much of questionnaire based bilingualism research. Substantively the survey showed that BFLA preschoolers spoke German better or spoke both languages equally well whereas ESLA preschoolers spoke Polish better. This result likely relates to the fact that (1) BFLA preschoolers used Polish in fewer interactions with parents than ESLA children and that (2) BFLA preschoolers mostly heard Polish from a single parent rather than two as was the case for ESLA children. The BFLA-ESLA difference thus made a difference to children's heritage Polish development and use already at age 3.5.